2003
DOI: 10.1097/00005537-200305000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Voice Quality After Laser Surgery or Radiotherapy for T1a Glottic Carcinoma

Abstract: Contrary to some reports, the voice quality is minimally affected by laser surgery for T1a glottic carcinoma, and outcome is similar to radiotherapy. The average fundamental frequency is higher than normal after laser surgery, but the effect on the quality of life was trivial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 21 publications
7
60
0
2
Order By: Relevance
“…No significant differences between TLM and RT were reported in these four studies. Eight studies used electro-acoustic voice analysis: five of these studies 12,15,16,20,21 found no significant differences between TLM and RT groups, while three studies [7][8][9] reported significantly better outcomes for RT.…”
Section: Voice Outcomesmentioning
confidence: 99%
“…No significant differences between TLM and RT were reported in these four studies. Eight studies used electro-acoustic voice analysis: five of these studies 12,15,16,20,21 found no significant differences between TLM and RT groups, while three studies [7][8][9] reported significantly better outcomes for RT.…”
Section: Voice Outcomesmentioning
confidence: 99%
“…A recent interesting study suggests the use of the electroglottography as an objective voice assessment in irradiated patients to overcome the limits of the self-assessment methods (VHI). This study demonstrated improvement of many key parameters over a 12-month period in 25 patients with T1/T2 glottic cancer who underwent radical radiotherapy [44]; further studies to validate this technique and its cost/effectiveness ratio should be provided.…”
Section: Discussionmentioning
confidence: 78%
“…The main problem of the comparative studies available about voice quality is bias in the selection criteria, due to the accurate preoperative and intraoperative diagnostic work-up available today. In fact, there is a distinct preference to treat patients with superficial T1a tumors with CO 2 laser and to reserve radiotherapy for the treatment of deeper infiltrating tumors [4,28,44,51]. A further issue concerns the differences in the follow-up periods because of the retrospective design of these studies.…”
mentioning
confidence: 99%
“…Although posttreatment voice quality is an important factor when choosing the treatment modality, which modality gives a better outcome is a controversial topic. Several articles compared posttreatment voice quality between laser cordectomy and RT [2,3,4,5,6,7,8,9,10,11,12,13], but they did not consider the type of cordectomy in detail. Laser cordectomy was classified into 6 types after the publication of the ELS classification.…”
Section: Discussionmentioning
confidence: 99%
“…Many published articles have described voice quality after each treatment modality. Some favored laser cordectomy [2,3], some favored RT [4,5,6,7], and others found these to be equivalent [8,9,10,11,12,13]. It is difficult to assess which treatment is better in terms of voice quality after treatment.…”
Section: Introductionmentioning
confidence: 99%